Computational modal analysis of a composite pelvic bone: convergence and validation studies. Issue 9 (4th July 2019) - Henyš, Petr; Čapek, Lukáš
Abstract: The purpose of the present study was to describe the structural density and geometry of the bone, as well as its sensitivity to the resolution of finite element discretisation. The study introduces a novel way to validate biomechanical model of the bone by experimental modal analysis. The structural density and geometry of the model was obtained from a composite bone. A detailed investigation of the weight dependence of the bone on the mesh resolution was performed to obtain the best match with the real weight of the tested bone. The computational model was compared with the experimental results obtained from the modal analysis. The overall changes of the modal properties and bone weight in the model caused by different mesh resolutions and order of approximation were below 10%, despite the bone was modelled with simple isotropic material properties. The experimental modal analysis shows a great potential to be a robust verification tool of computational biomechanical models because it provides boundary conditions–free results. The sensitivity analysis revealed that the linear approximation of the density field is not suitable for the modelling of the modal response of composite bone.